Aesthetic values of island tourism in Malaysia's east coast region: does duration of stay matter in satisfying tourists? - Saad, Mazni; Lokman, Ainun Khadijah; Ong, Mohd Hanafi Azman; Othman, Nor'Ain (2021)
Island tourism is popular in Malaysia among both local and international visitors. Terengganu, Kelantan, and Pahang state islands are becoming increasingly popular as world-class nature tourism destinations. The East Coast islands of these three states that face the South China Sea have become full-fledged nature tourism destinations. They are naturally beautiful and accessible, among other things, attract and appear as a destination image. However, tourist loyalty is being questioned in terms of duration of stay when tourism activities may impact the nature of the islands. Thus, the purpose of this research is to investigate the relationship between Aesthetic Qualities (Cleanliness, Scenery, Art/Architecture, and Genuineness) and Tourist Satisfaction. The study has two research objectives (1) to determine whether aesthetic qualities affect tourist satisfaction in Malaysia's East Coast islands and (2) to investigate which aesthetic qualities have a significant impact on tourist satisfaction in Malaysia's East Coast islands. This study used a quantitative approach based on a cross-sectional approach and collected 150 responses (39% response rate) from tourists who had visited any one of these islands in the past three years. Smart PLS-SEM analysis was used. After the 5000 replications of samples, the analysis reveals that all aesthetic qualities (cleanliness, scenery, art/architecture, and genuineness) contributed to tourist satisfaction when visiting the East Coast region's islands. ANOVA analysis, supported by the post hoc multiple comparison analysis among the groups, the Least Square Difference (i.e., LSD) Fisher's Test, and Games-Howell Test, yielded intriguing results for the significant difference between the duration of stay groups on the islands. The duration of stay, scenery, architecture, and satisfaction showed significant differences, but the tourists' perception is better during the short stay. The findings would raise public awareness about the importance of the sustainability of aesthetic value of island tourism while also benefiting many stakeholders. Therefore, more promotional efforts should be invested in extending the duration of tourists' stay. However, the generalisations of results in this paper are limited to responses given mainly from three main islands of Terengganu.